Limonoids isolated from fruits of Carapa guianensis Aublet (Meliaceae) - Silva, Suniá Gomes; Nunomura, Rita de Cássia Saraiva; Nunomura, Sergio Massayoshi (Química Nova, 2012)
Six limonoids were isolated in hexane extract obtained from the seeds and pericarps of Carapa guianensis. The structures of the limonoids were determined based on the analysis of High Resolution Mass Spectroscopy and Nuclear Magnetic Resonance (uni-and bi-dimensional experiments) data. This is the first report of isolation of the limonoid 6-acetoxy-7-deacetilgedunin from the seeds of the C. guianensis species. The limonoid 6-hydroxy-methyl angolensate was also described for the first time in this species.
Limonoides isolados dos frutos de Carapa guianensis aublet (Meliaceae)